PENGARUH MEDIA DIORAMA EKOSISTEM TERHADAP HASIL BELAJAR IPAS KELAS IV DI SD NEGERI 6 BUMI NABUNG ILIR - Yuniadi, Ningrum Fadillah; Aris, Ika Evitasari; Rahayu, Maulina (LPPM Universitas Bina Bangsa, 2025)
This study aims to examine the effect of ecosystem diorama media on the learning outcomes of fourth-grade students in Natural and Social Sciences (IPAS) at SD Negeri 6 Bumi Nabung Ilir. The research problem arose from low student achievement due to the dominance of verbal methods and limited media variation. A quantitative approach with a One Group Pretest-Posttest design was employed. The sample consisted of 22 students, with multiple-choice tests administered before and after learning using diorama media. Data were analyzed using descriptive statistics, normality test, homogeneity test, and paired sample t-test. The results showed a significant increase in learning outcomes, with the average score rising from 47.27 (pretest) to 84.55 (posttest). Students in the high category reached 50%, medium 45.45%, and low 4.55%. The t-test confirmed a significant effect of diorama media. It is concluded that ecosystem dioramas effectively improve concept understanding and student motivation in IPAS learning.